Evaluation of the continuity of Iraqi banks listed in the Iraq Stock Exchange using indicators of financial failure - Ali Abdul Wahed Khalaf; Hussein Ali Abdul Wahed (Journal of Madenat Alelem University College, 2022)
The research aims to use indicators of financial failure in assessing the continuity of banks, as Iraqi banks are among the first institutions and companies that have tended to implement international standards, in addition to being committed to principles and assumptions in the accounting field and facing many and varied risks. Perhaps one of the most dangerous is financial failure, so we find that the prediction of failure financial engages all the authorities related to banks, especially researchers and those interested in this subject, to develop models to be used in assessing the continuity of banks . One of these models is the (kida) model, which is used in assessing the continuity of banks and their ability to meet their obligations and carry out their duties through a set of financial ratios that distinguish between banks those who succeed in their doubtful ability and which are exposed to financial failure, and to know the nature of their activities early.From this standpoint, one of the main objectives of the research is to identify the extent of the effectiveness of using the (Kida) model in evaluating the continuity of banks by ascertaining whether the banks were exposed to financial failure or no, in order to achieve this goal, the two researchers used some financial statements of the banks, the sample of the research, and the research problem was represented by paltry The following question: Does the (Kida) model reveal to us the risks of financial failure facing commercial banks listed in the Iraq Stock Exchange by evaluating their continuity in the exercise of their commercial activity in the foreseeable future? The Kida model was applied to a sample of three Iraqi banks using financial ratios, and at the end of the analysis some conclusions and recommendations were drawn up that emphasize the need for banks to adopt financial analysis models to know the results of their work in terms of predicting financial failure.